When and How Should Agricultural Insurance Be Subsidized? : Issues and Good Practices - Hazell, Peter; Sberro-Kessler, Rachel; Varangis, Panos (International Labour Organization and the International Finance Corporation, 2019)
Agricultural insurance, defined here to include crop and livestock insurance, is an instrument of choice in many countries for helping farmers and rural communities cope with risk. This paper explores the reasons why governments and donors subsidize agricultural insurance, and asks: (a) is this a worthwhile way to spend public money, and (b) if insurance must be subsidized are there smarter ways of doing it that can achieve the same objectives, but at lower cost, and which avoid some of the economic and institutional pitfalls that have plagued subsidized agricultural insurance in the past. The paper is structured as follows: section one gives introduction. Section two reviews existing types and levels of subsidies for agricultural insurance, both globally and for the developing world. Section three reviews the various arguments that have been offered for subsidizing agricultural insurance, while section four discusses some of the key challenges that have arisen when insurance subsidies are poorly designed. Section five seeks to balance the benefits and costs of subsidized agricultural insurance, and asks whether this has proven to be a worthwhile way of spending public funds. Section six presents a set of guiding principles and best practices to be used in their design and implementation. Finally, section seven concludes.